11x-27=6x-7-5x

Simple and best practice solution for 11x-27=6x-7-5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11x-27=6x-7-5x equation:


Simplifying
11x + -27 = 6x + -7 + -5x

Reorder the terms:
-27 + 11x = 6x + -7 + -5x

Reorder the terms:
-27 + 11x = -7 + 6x + -5x

Combine like terms: 6x + -5x = 1x
-27 + 11x = -7 + 1x

Solving
-27 + 11x = -7 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-27 + 11x + -1x = -7 + 1x + -1x

Combine like terms: 11x + -1x = 10x
-27 + 10x = -7 + 1x + -1x

Combine like terms: 1x + -1x = 0
-27 + 10x = -7 + 0
-27 + 10x = -7

Add '27' to each side of the equation.
-27 + 27 + 10x = -7 + 27

Combine like terms: -27 + 27 = 0
0 + 10x = -7 + 27
10x = -7 + 27

Combine like terms: -7 + 27 = 20
10x = 20

Divide each side by '10'.
x = 2

Simplifying
x = 2

See similar equations:

| 5+2x=66 | | 1.2+0.1x=0.4x-4.2 | | 10n+8s=50 | | 3=-20x+2 | | c-0.55c=54 | | 6u+8=8u | | X-1=y*4000 | | 6=2(v+5)-6v | | p+0.04p=114.4 | | .04x=.26 | | 63-2v=7v | | g(z)=-5z-5 | | .04x=26 | | Y=2x^2+12x+20 | | 6y+3x=93 | | 42=8x-(4x-8)+7(x-3) | | -24-3x=-3+4(1-2x) | | 0.25p-4.5=3 | | d=30(15) | | 55y+8x=90 | | 5(2x+3)+3=3(2x+6)-10 | | 60x+11y=1 | | x/27=26 | | X+2=y*5000 | | d=25(20) | | 27/x=26 | | -10-9h-10=-6h+100 | | 0.25p-4.6=3 | | 18+22=-5(7x-8) | | 3X-6whenX=4 | | x+10x-70=2x+3 | | 2(5x-3)-3=6(2x-3)-10 |

Equations solver categories